Faktori koji utiču na primenu augmentativne i alternativne komunikacije - Slavković, Sanela; Veselinovic, Mila; Ivezic, Stasa; Uzelac, Jovana (Specijalna edukacija i rehabilitacija, 2024)
Augmentative and alternative communication (AAC) includes various methods, strategies, and techniques as well as devices and means developed with the aim of imroving the communication competence of people with speech and language disorders. AAC intervention implies a carefully planned process of selection and implementation of AAC means, as well as a precise definition of outcomes and methods of their evaluation to improve an indiidual’s participation in the communication process. This paper aims to point out factors (personal and environmental) which potentially represent facilitators or barriers that influence the application of augmentative and alternative communication. Personal factors of importance include the user’s individual characteristics, ability and skill set, personality traits and motivation, as well as personal preferences. The environmental factors include physical and cultural environment, socioeconomic status, knowledge, information and attitudes of the environment, experts’ competence, and technology-related factors. Reported factors must be taken into account when implementing the AAK intervention as an effective support strategy for people with severe forms of speech and language disorders.